Nghiên cứu sử dụng một số thảo mộc làm thuốc trừ sâu - Lan Oanh, Lê Thị; Hằng, Hoa Thị; Thơm, Trần Thị; Tĩnh, Nguyễn Hoàng; Thiết, Nguyễn Văn; Thụ, Nguyễn Xuân (VNU Journal of Science: Natural Sciences and Technology, 2000)
Abstract